Resistance to Powdery Mildew in Qingke Involves the Accumulation of Aromatic Phenolamides Through Jasmonate-Mediated Activation of Defense-Related Genes - Xu, Congping; Zhan, Chuansong; Huang, Sishu; Xu, Qijun; Tang, Tang; Wang, Yulin; Luo, Jie; Zeng, Xingquan (Frontiers in Plant Science, 2022)
Powdery mildew (PM) leads to severe yield reduction in qingke (Hordeum vulgare L. var. nudum). Although studies have focused on identifying PM-related resistance genes, mechanistic insights into the metabolic regulation networks of resistance against PM have rarely been explored in qingke. Here, we integrated transcriptomic, proteomic and metabolomic data using PM-susceptible (G72) and PM-resistant (K69) accessions to systemically explore the mechanisms of PM resistance. The integrated results show that a rapidly transduction of jasmonic acid (JA) and (+)-7-iso-jasmonoyl-L-isoleucine (JA-Ile), and importantly, a inducing accumulation of aromatic PAs conferred qingke-specific resistance for PM stress. Functional analysis revealed that the four BAHD N-acyltransferase genes were responsible for the synthesis of aliphatic and aromatic PAs. The expression of the four genes are induced by methyl jasmonate (MeJA) and PM treatment. Co-expression network analysis shows that a histone lysine demethylase, JMJ705 gene, also induced by MeJA and PM treatment, had highly correlation with PAs biosynthesis. Chromatin immunoprecipitation (ChIP)-seq assays revealed that the level of trimethylated histone H3 lysine 27 (H3K27me3) of the four genes in MeJA and PM-treated plants was significantly reduced. Overall, our results suggest that a novel strategy for jasmonic acid signal-mediated demethylation controlling the accumulation of aromatic PAs to enhance plant immune resistance through removal of H3K27me3 and activating defense-related gene expression.